Profits, Planes and Policy: An Analysis of the Midway Airport Privatization and its Implications for Future Airport Privatizations in the United States - Cartmell, Sarah (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Midway International Airport in Chicago is poised to become the first large hub U.S. airport to be privatized through a 99-year lease and concession to the private sector. This precedent-setting airport privatization presents America's air transportation and infrastructure investment communities with a rich opportunity for discerning the immediate impact and broader implications of a domestic airport privatization. The Midway Airport privatization crests a confluence of forces that have made airport privatization an attractive and viable option for meeting the current and future needs of airports, and those of their public owners. America's aviation infrastructure requires far-reaching and expensive upgrades at a time when traditional airport financing modes are falling short. Further compounding this development are the mounting pressures on public budgets that serve to relegate infrastructure spending to a second-tier priority. At the same time, global infrastructure investors have amassed the money and trained their sights on transportation assets that provide steady cash flows. Both demand and supply line up to create an investment climate conducive to airport privatization. However, the theoretical arguments supporting and opposing airport privatization reveal a host of unresolved issues that serve to render airport privatization no panacea to the challenges facing the system. Instead, the theory and previous airport privatization experiences -- both domestic and international -- highlight the difficulty of undertaking a privatization and the inherent trade-offs involved. Most importantly, limited competition among airports makes efficiency gains under private ownership a questionable outcome. Against this backdrop, the Midway Airport privatization was structured and pursued to maximize upfront financial gain to the City of Chicago. This approach is problematic for several reasons: It reduced future revenue streams from the airport to the city; forced the city to incur ongoing financial obligations at Midway Airport that whittle down the amount netted from the transaction; and increased the risk of an overvaluation that will make it difficult for MIDCo to earn reasonable returns, thus ensuring precipitous price increases for airport users. While predicting the future financial and operational performance of a privatized Midway is difficult, the unresolved issues outlined above should give pause to other public airport owners considering airport privatization. The Midway International Airport privatization demonstrates that future airport privatizations in the United States should evolve beyond the narrow motive of immediate revenue generation to assume a structure that secures the diversion of long-term sustainable cash flows from the privatized airport and that provides for more competition and efficiency gains. Addendum: On April 20, 2009, the City of Chicago announced that the 99-year lease and concession of Midway Airport to MIDCo had collapsed. According to the city, MIDCo was unable to secure the financing necessary to make its $2.521 billion upfront payment to the city. Current city Chief Financial Officer Gene Saffold said the deal's collapse was attributable to the global economic crisis and liquidity crunch, which had severely impacted the availability of financing. Saffold also stated the city's intention to re-bid Midway Airport when market conditions improve.